Turning strategies for the bounding quadruped robot with an active spine. Issue 5 (20th August 2018) - Wei, Zhong; Song, Guangming; Sun, Huiyu; Qi, Qien; Gao, Yuan; Qiao, Guifang
Abstract : Purpose: This paper aims to study the turning strategies for the bounding quadruped robot with an active spine and explore the significant role of the spine in the turning locomotion. Design/methodology/approach: Firstly, the bounding gait combining the pitch motion of the spine with the leg motion is presented. In this gait, the spine moves in phase with the front legs. All the joints of the legs and spine are controlled by cosine signals to simplify the control, and the initial position and oscillation amplitude of the joints can be tuned. To verify the effectiveness of the proposed gait, the spine joints are set with different initial positions and oscillation amplitudes, and the initial position and oscillation amplitude of the leg joints are tuned to make the virtual model do the best locomotion in terms of the speed and stability in the simulation. The control signals are also used to control a real robot called Transleg. Then, three different turning strategies are proposed, including driving the left and right legs with different strides, swaying the spine in the yaw direction and combining the above two methods. Finally, these strategies are tested on the real robot. Findings: The stable bounding locomotion can be achieved using the proposed gait. With the spine motion, the speed of the bounding locomotion is increased; the turning radius is reduced; and the angular velocity is increased. Originality/value: A simple and flexible planning of the bounding gait and three turning strategies for the bounding quadruped robot are proposed. The effectiveness of the proposed bounding gait, along with the beneficial effect of the spine motion in the yaw direction on the turning locomotion is demonstrated with the computer simulations and robot experiments. This will be instructive for the designing and actuating of the other quadruped robots.